TEMPO-oxidized cellulose poly-ionic drawn fiber, a cell support system proof of concept - Rios, Mariana Alves; Barbugli, Paula Aboud [UNESP]; Iemma, Mônica Rosas Costa; Grande, Rafael; Carvalho, Antônio José Felix; Trovatti, Eliane (Springer Nature, 2021)
The development of new cell carrier systems is crucial for application in regenerative medicine, once they deliver the cells to the injured tissue to trigger the repair and stimulate the regeneration. Here we report the preparation of a cell carrier system in fiber shape, in which the cells osteo-1 are incorporated. For the fiber formation, the oxidized cellulose nanofibers suspension loaded with cells is complexed with calcium ions in a pulling process giving rise to the fiber loaded with cells, with dimensions which allow it to handle. The microscopic images showed the success of the proposed method to incorporate the cells into the fibers. The results of the in vitro viability tests indicated the capability of the fibers to keep the cells alive and to mineralize them, indicating that their osteogenic capability was not affected. In addition, the fiber disintegration studies showed the system is capable of releasing the cells, suggesting the potential of the fibers as a new assembled hydrogel carrier cell therapy.